Immune Parameters of Dry Cows Fed Mannan Oligosaccharide and Subsequent Transfer of Immunity to Calves - Franklin, S.T. (J Dairy Sci, 2005)
The objective of this study was to evaluate the benefits of supplementation of mannan oligosaccharide (MOS) to cows during the last 3 wk of the dry period on immune function of the cows and subsequent transfer of passive immunity to their calves. Indicators of nonspecific and specific immunity were evaluated. Cows were vaccinated against rotavirus at 4 and 2 wk before expected parturition. Blood samples were obtained from cows before vaccination and at weekly intervals until calving and from calves at birth and 24 h for analysis of serum protein concentrations, packed cell volume, white blood cell counts, white blood cell differentials, and serum rotavirus neutralization titers. Colostrum quantity and quality were measured at calving, and immunoglobulin isotype concentrations in colostrum were determined. Specific immunity was enhanced by MOS supplementation as evidenced by greater serum rotavirus neutralization titers at calving in cows supplemented with MOS compared with control cows. Colostral rotavirus neutralization titers were not affected by treatment. Although numerical differences appeared large, there was a high degree of variability in the colostral rotavirus neutralization titers. Calves from cows fed MOS tended to have greater serum rotavirus neutralization titers compared with calves from cows fed the control diet. There was a tendency for greater increases in serum protein concentrations from birth to 24 h in calves from cows fed MOS compared with calves from cows fed the control diet. Results indicate that supplementation of MOS to cows during the dry period enhanced their immune response to rotavirus and tended to enhance the subsequent transfer of rotavirus antibodies to calves.